Příklady z matematiky

Každé načítání stránky vám zadá nové příklady !




Jméno:_____________________________
 
X + Y - Z = 33
Z + Y + X = 127
Z + X - Y = 27

X=
Y=
Z=






X + Y - Z = 21
Z + Y + X = 113
Z + X - Y = 75

X=
Y=
Z=






X + Y - Z = 30
Z + Y + X = 78
Z + X - Y = 56

X=
Y=
Z=






X + Y - Z = 42
Z + Y + X = 62
Z + X - Y = -10

X=
Y=
Z=






X + Y - Z = 38
Z + Y + X = 100
Z + X - Y = 58

X=
Y=
Z=






X + Y - Z = -2
Z + Y + X = 26
Z + X - Y = 4

X=
Y=
Z=






X + Y - Z = 22
Z + Y + X = 26
Z + X - Y = -12

X=
Y=
Z=






X + Y - Z = 14
Z + Y + X = 60
Z + X - Y = 28

X=
Y=
Z=






X + Y - Z = 35
Z + Y + X = 69
Z + X - Y = 61

X=
Y=
Z=